2015
DOI: 10.1007/s00441-015-2266-9
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 and S100A10 in the mammalian oviduct

Abstract: In many mammals upon entry on the female reproductive tract a subpopulation of sperm is stored in the oviduct forming a functional reservoir. In the oviducts of pig and cow, Annexin A2 (AnxA2) has been linked to the binding of sperm. This protein may exist as a monomer or bound to S100A10, and both forms are associated with different biological functions. S100A10 has not yet been reported in the oviduct. The objective of this work was to analyze for the presence of S100A10 in the oviduct and advance in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…In this study, a total of 30 and 24 proteins were found to be more abundant at Pre-ov compared with Post-ov in ipsi-and contralateral oviducts respectively. Annexins A1 (ANXA1) and A2 (ANXA2), previously recognized as membrane proteins expressed at the apical side of oviductal epithelial cells in the bovine (Teijeiro et al 2016), were among the most abundant proteins before ovulation. Antibodies directed against annexins A1 and A2 were shown to inhibit the binding of bull sperm to explants of oviductal epithelium, placing these proteins as strong candidates for interaction with spermatozoa in vivo (Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 30 and 24 proteins were found to be more abundant at Pre-ov compared with Post-ov in ipsi-and contralateral oviducts respectively. Annexins A1 (ANXA1) and A2 (ANXA2), previously recognized as membrane proteins expressed at the apical side of oviductal epithelial cells in the bovine (Teijeiro et al 2016), were among the most abundant proteins before ovulation. Antibodies directed against annexins A1 and A2 were shown to inhibit the binding of bull sperm to explants of oviductal epithelium, placing these proteins as strong candidates for interaction with spermatozoa in vivo (Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, proteins of oviductal origin, including oviductin (human) and Annexin A2 and S110A (human and a range of species), are transferred to the sperm cell surface rendering them competent for fertilization [36]. It is equally likely that proteins or other mediators, are transferred to sperm during their passage through the uterine cavity.…”
Section: Establishment Of Pregnancy: the Importance Of The Uterine MImentioning
confidence: 99%
“…) that are able to attach biological structures (Teijeiro et al. ). Annexins have also been related to exocytosis, endocytosis, linkage between membranes or between membranes and the cytoskeleton (Teijeiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teijeiro et al. () reported the detection of annexin A2 and S100A10 in the oviduct of cow, rabbit, pig, dog and cat oviduct. Likewise, in the present study, the peak that possibly corresponds to annexin A2 was also detected in the cilia of epithelial cells, with different distribution in the infundibulum and ampulla and a minor abundance in the isthmus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation